Sikap Dan Perilaku Masyarakat Desa Dajan Peken Dalam Pengelolaan Sampah Rumah Tangga - Laksmiwati, Ida Ayu Alit; Wedasantara, Ida Bagus Oka; Budarsa, Gede (Bumi Lestari; Vol 24 No 1 (2024), 2024)
Population growth in urban area directly or indirectly affects environmental quality. Waste is environmental problem that has long been of global concern and needs to be handled seriously so that it does not cause harmful impacts. Currently, waste in Bali Province is not only a problem in urban area, but has spread to rural area. Responding to the Bali Provincial government's policy, Dajan Peken Village in Tabanan Regency has established a TPS3R (Reuse-Reduce-Recycle Waste Management Site) for waste management with several waste management facilities and infrastructure. This research aims to identify community attitudes in source-based waste management, and understand community behavior in managing their respective household waste in Dajan Peken Village. The results of the research show the peoples in Dajan Peken Village already have a fairly good attitude in responding to Bali Governor Regulation No. 47 of 2019 concerning Source-Based Waste Management, however, public views regarding conventional waste management such as landfilling and burning can still be found. At the behavioral level, patterns of inappropriate waste management are still found in Dajan Peken Village, such as burning waste, hoarding it, not sorting waste, and so on.